Mitigation of the Seismic Impact on Storage Gas Tanks by Using Isolation System - Henriques, Jose; Morelli, Francesco; Degée, Hervé (Periodica Polytechnica Civil Engineering, 2022)
The paper presents the studies carried out on a big storage gas tank for the seismic vulnerability assessment and the retrofit through isolation system. This Gasometer, constructed in the early eighties, consists in a steel cylinder of 70 m height and 44 m diameter. The tank bearing structure is composed by a classical steel frame closed with curved steel plates. Inside the tank, a piston-fender and rubber sealing system allow the variation of the container volume and control the gas pressure. The latter represents half of the seismic mass and its position can vary along the tank height. The seismic vulnerability of the steel structure of the Gasometer on its as-it-is state is assessed through the execution of Incremental Dynamic Analyses, placing particular attention on the definition of possible limit states. Subsequently, the seismic retrofit through base isolation system, adopting Double Curved Surface Sliders, is proposed and numerically assessed. The results and comparison between the as-it-is state and the retrofitted state supplies important information about the effectiveness of base isolation for the risk mitigation of gas tanks.